Hidden Curriculum dalam Pembelajaran Sejarah dan Penanaman Nasionalisme - Dyah Kumalasari (ISTORIA: Jurnal Pendidikan dan Sejarah, 2015)
This study aims to flash back on the extent of the hidden curriculum in the teaching of history can affect the formation of the spirit of nationalism among students/students in university. The method used in conducting this research is descriptive qualitative method. The results showed that the plurality of the Indonesian nation as objective conditions, particularly with regard to ethnicity, religion, culture, and language appears to be very vulnerable and would potentially be the cause of disintegration. The concept of the hidden curriculum includes the development of values in school attention and emphasis varies according to the level of lecturers spirit and physical condition as well as the social climate of the school/college. The concept of hidden curriculum in history teaching aims to rebuild the bond of nationality (rebuilding the nation), which is the problem of rebuilding the humanities, society, and culture. In this respect the role of parents and the community in growing nationalism in the context of the hidden curriculum is needed.Keywords: Hidden Curriculum, Teaching History, Nationalism Soul.